What happens when patients say “no” to offers of referral for weight loss? - Results and recommendations from a conversation analysis of primary care interactions - Albury, C; Webb, H; Ziebland, S; Aveyard, P; Stokoe, E (Elsevier, 2021)
Objective Guidelines recommend that clinicians should offer patients with obesity referrals to weight management services. However, clinicians and patients worry that such conversations will generate friction, and the risk of this is greatest when patients say no. We examined how doctors actually respond to patient refusals, and how patients reacted to clinicians in turn.